2015
DOI: 10.1123/ijsnem.2014-0129
|View full text |Cite
|
Sign up to set email alerts
|

Acute Beetroot Juice Supplementation Does Not Improve Cycling Performance in Normoxia or Moderate Hypoxia

Abstract: Beetroot juice (BR) has been shown to lower the oxygen cost of exercise in normoxia and may have similar effects in hypoxia. We investigated the effect of BR on steady-state exercise economy and 10-km time trial (TT) performance in normoxia and moderate hypoxia (simulated altitude: ~2500 m). Eleven trained male cyclists (VO 2peak ≥ 60 ml · kg(-1) · min(-1)) completed four exercise trials. Two hours before exercise, subjects consumed 70 mL BR (~6 mmol nitrate) or placebo (nitrate-depleted BR) in a randomized, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
71
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(81 citation statements)
references
References 0 publications
8
71
1
1
Order By: Relevance
“…Consistent with previous investigations, plasma nitrate and nitrite, and exhaled NO concentrations were significantly elevated following dietary nitrate supplementation [1,2,5,8,55,22,39,38], signifying an increase in the 'substrates' available for NO generation via the nitrate-nitrite-NO pathway [11]. Peak plasma nitrite concentration was 602 % higher in BRJ versus PLA, similar to Arnold et al [38] (775 %) (~ 7 mmol nitrate), but considerably greater than reported by Muggeridge et al [22] (134 %) (~ 5 mmol nitrate) and Vanhatalo et al [8] (150 %) (~ 9.3 mmol).…”
Section: Plasma Nitrate Nitrite and Exhaled Nosupporting
confidence: 90%
See 4 more Smart Citations
“…Consistent with previous investigations, plasma nitrate and nitrite, and exhaled NO concentrations were significantly elevated following dietary nitrate supplementation [1,2,5,8,55,22,39,38], signifying an increase in the 'substrates' available for NO generation via the nitrate-nitrite-NO pathway [11]. Peak plasma nitrite concentration was 602 % higher in BRJ versus PLA, similar to Arnold et al [38] (775 %) (~ 7 mmol nitrate), but considerably greater than reported by Muggeridge et al [22] (134 %) (~ 5 mmol nitrate) and Vanhatalo et al [8] (150 %) (~ 9.3 mmol).…”
Section: Plasma Nitrate Nitrite and Exhaled Nosupporting
confidence: 90%
“…Therefore, the high nitrate dose administered in this study relative to investigations which have not observed an effect of nitrate supplementation (~ 5 -7 mmol) [38][39][40] may have also contributed towards the consistent ergogenic effect observed here.…”
Section: Effect Of Nitrate Supplementation On Running Performance In supporting
confidence: 64%
See 3 more Smart Citations